Front Cover: Maytansinol Functionalization: Towards Useful Probes for Studying Microtubule Dynamics (Chem. Eur. J. 5/2023). Issue 5 (17th January 2023) - Boiarska, Zlata; Pérez‐Peña, Helena; Abel, Anne‐Catherine; Marzullo, Paola; Álvarez‐Bernad, Beatriz; Bonato, Francesca; Santini, Benedetta; Horvath, Dragos; Lucena‐Agell, Daniel; Vasile, Francesca; Sironi, Maurizio; Díaz, J. Fernando; et al.
Abstract : Work with the elements of nature : Our building block, maytansinol, represented as a constellation of stars, is the main protagonist of the story. A ray of light coming out from it demonstrates how different moieties can be attached to it, opening new horizons. As maytansinoids show a destabilising effect on microtubules, we represent the latter by trees. The tree trunk is a microtubule, from which the tubulins are disassembling into the leaves. The TubInTrain logo in the corner represents the H2020‐MSCA‐ITN‐2019 network that made this interdisciplinary investigation possible. More information can be found in the Research Article by S. Pieraccini, D. Passarella and co‐workers. (DOI: 10.1002/chem.202203431 ). Created with BioRender.com.